On tyranny : twenty lessons from the twentieth century - Snyder, Timothy (New York : Tim Duggan Books, 2017)
The Founding Fathers tried to protect us from the threat they knew, the tyranny that overcame ancient democracy. Today, our political order faces new threats, not unlike the totalitarianism of the twentieth century. We are no wiser than the Europeans who saw democracy yield to fascism, Nazism, or communism. Our one advantage is that we might learn from their experience.
Keywords: Historia moderna; Totalitarismo; Moralidad de la clase política; Democracia